Correlation of the cd36 rs1761667 Polymorphism and Lifestyle Factors with Fatty Acid Perception Threshold - Dionysius Subali; Elena Soegiarto; Ardy Lizuardi; Rendy Dijaya; Felicia Kartawidjajaputra; Lina Antono; Richie Delano (Journal of Health and Nutrition Research, 2026)
Genetic variations, such as in the CD36 gene (rs1761667), may influence fat perception and dietary patterns, contributing to obesity. This cross-sectional study involved 87 office workers who underwent genotyping for cd36 rs1761667, sensory testing for oleic acid perception threshold, and assessments of body composition, physical activity, and dietary intake. No direct association was found between the cd36 rs1761667 genotype and the fatty acid perception threshold (p > 0.05). However, stratified analyses revealed that men carrying the A allele (GA/AA, n=23) had a higher body fat percentage compared to those with the GG genotype (n=11). In women, GA/AA carriers consumed more protein, while GG carriers derived a higher proportion of energy from carbohydrates. Among overweight individuals, GG carriers reported higher carbohydrate intake than A allele carriers (p=0.026). These findings suggest that while cd36 rs1761667 may not be a primary determinant of fat taste sensitivity in this cohort, it may contribute modestly to body fat composition and dietary behaviors through interactions with gender and BMI status.